Islamic Education Marketing Management - Holilur Rahman; Madhar Amin; Mustaminah (LECTURES: Journal of Islamic and Education Studies, 2024)
In an era of increasingly fierce competition, Islamic educational institutions are considered as the main producers of Islamic education services that must market their services to consumers, namely students  and student guardians, as well as other related parties. The success of an Islamic educational institution in maintaining its existence is highly dependent on its ability to market its educational services well, fulfill consumer needs, provide added value for individual development, and create a good image in the eyes of the community. This research aims to examine the concept and importance of marketing management in the context of Islamic educational institutions. This research uses a descriptive qualitative approach to collect data and analyze the concept of Islamic education marketing management. Data were collected through searching related literature from various sources. The results show that Islamic education marketing management is an effort to plan, implement and supervise marketing activities in Islamic education institutions in order to achieve organizational goals efficiently and effectively. The concept of Islamic education marketing management involves the strategy of determining the target market, competitive market position, and marketing mix which includes product, price, place, promotion, human resources, physical evidence, and process. By implementing the right marketing strategy, Islamic education institutions can increase their attractiveness, maintain their sustainability, and provide quality and relevant educational services for the community. This research makes an important contribution to the understanding of the importance of marketing management in the context of Islamic educational institutions. The implications of this research are expected to be the basis for developing effective marketing strategies in improving the existence and quality of Islamic education services in the community.